(untitled) (Acta Polytechnica CTU Proceedings, 2022)
This study analyses moisture dry-out from a steel-faced insulated sandwich panel by forced convection. Moisture convection performance was studied by laboratory tests and simulation. Two test walls with the lower parts close to the free water level were studied in a laboratory with and without convection. In addition, a real-scale wall was built to south orientate direction. Measurements were also used for simulation model calibration. The hygrothermal simulations were performed with the simulation tool Delphin in stable climatic conditions to determine the magnitude of the convection moisture dry-out capacity. Comparison of the measured and simulated relative humidity showed sufficiently good agreement. The results indicate that convection significantly improves dry-out capacity, especially during summer. However, during autumn and winter their dry-out capacity was smaller. To minimise the wetting of insulation, weather protection during construction and storage is necessary.